A triphenylcyclopropenylium mass tag: synthesis and application to ultrasensitive LC/MS analysis of amines12. Issue 11 (21st April 2016) - Topolyan, Artyom P.; Strizhevskaya, Dina A.; Belyaeva, Maria A.; Brylev, Vladimir A.; Ustinov, Alexey V.; Formanovsky, Andrey A.; Korshun, Vladimir A.
Abstract : Thiol adducts of triphenylcyclopropenylium undergo efficient heterolytic dissociation in electrospray (ESI) or laser desorption ionization (LDI) mass spectrometry giving rise to a prominent signal of an aromatic C3 Ph3 + cation. Abstract : Thiol adducts of triphenylcyclopropenylium undergo efficient heterolytic dissociation under conditions of both electrospray (ESI) and laser desorption ionization (LDI) mass spectrometry giving rise to a prominent signal of an aromatic C3 Ph3 + cation. A functionalized mass tagging reagent, an activated ester carrying an S-linked C3 Ph3 unit, has been developed and used for the derivatization of amines and their subsequent HPLC/ESI-MS detection in low attomolar amounts.